Uncertainty Analysis Study on Seakeeping Tests of Benchmark Model. Issue 1 (1st September 2022) - Rizal, Nandiko; Sari, Dian Purnama; Cahyono, Beny; Prastyo, Dedy Dwi; Ali, Baharuddin; Arianti, Erdina
Abstract: Experimental uncertainty and measurement, particularly in engineering, have been increasingly emphasized over the last 20 years. Uncertainty analysis of ship model testing in seakeeping experiments based on International Organization for Standardization, Guide for Uncertainty of Measurements (ISO-GUM), report with recommendations published by ITTC (2008). In this paper, the uncertainties for free-running tests were performed for a model scale 1:62 as a benchmark model test at the Indonesian Hydrodynamic Laboratory (IHL). The benchmark model is representative of a full scale of 186 meters. The model has full appendages as well as a rudder and propellers to allow for free-running tests, natural roll period, free roll decay, and swing tests. Factors of basic uncertainty (type A and type B) are estimated using model tests. The standard deviation of the mean value of a repeated measurement is uncertainty type A. However, Type B uncertainty is estimated from manufacturing specifications. The uncertainty components resulting from both types are quantified by standard deviations. The uncertainty value of Type B is approximated by a corresponding variance. This study helps to understand the underlying uncertainty associated with this research, which resulted in a total geometry uncertainty value (Lpp, B, T, H, KG ¯, and kyy ) of 0.17598% and the total uncertainty value of the instrument calibration results (wave height sensor and qualysis motion tracking) is 0.01161%. The results of this study are expected to minimize the impact of sources of uncertainty and allow the potential for underlying uncertainty to be corrected for the next seaworthiness test.